Clinical skills documentation guide for athletic training - Hauth, John M.; Gloyeske, Brian M.; Amato, Herb 1956- (Slack Incorporated, 2016)
"Clinical Skills Documentation Guide for Athletic Training, Third Edition is an invaluable resource for athletic training students to learn, practice, and master clinical skill sets throughout their educational career. John Hauth, Brian Gloyeske, and Herbert Amato have updated the Third Edition to allow for easier integration into the classroom, laboratory activities, and clinical assessment. The organization of skills around EC5 including crosswalk information from the latest BOC Role Delineation Study better aligns the Third Edition skills sheets with commonly used texts and reference materials"--